Microbial contamination of raw meat and its environment in retail shops in Karachi, Pakistan - Hassan Ali, Nafisa; Farooqui, Amber; Khan, Adnan; Khan, Ameera Yahya; Kazmi, Shahana Urooj (The Journal of Infection in Developing Countries, 2010)
Background: This study was conducted to examine the frequency of contamination in retail meat available in Karachi, Pakistan. Methodology: Raw meat samples (250) and surface swabs (90) from meat processing equipment and the surrounding environment were analyzed for microbiological contamination. Results: Out of 340 samples, 84% were found to be contaminated with bacterial species, including Klebsiella, Enterobacter, Staphylococcus aureus and Bacillus subtilis. A total of 550 (66%) of the bacterial isolates were potential pathogens. Of these, 342 and 208 isolates were from meat and environmental samples respectively. Food-borne pathogens isolated from meat samples included Escherichia coli O157:H7, Listeria, Salmonella Enteritidis and Shigella species whereas environmental samples yielded Staphylococcus aureus and Shigella species. Four strains of Brucella species were also isolated from meat samples. Total aerobic counts ranged between 108 -1010 CFU/g or cm2. Resistance to a wide range of antibiotics was observed. Resistance rates to ampicillin, amoxicillin, novobiocin and cefaclor were from 62 to 75% in general. Thirty-three percent of Salmonella isolates were resistant to ampicillin. No quinolone resistance was observed. Biofilm formation was observed among 88 (16%) pathogenic bacteria including E. coli, Klebsiella, Enterobacter species and Staphylococcus aureus. Conclusions: Food-borne pathogens found in retail shops could be sources for horizontal contamination of meat. Our data confirm the circulation of antibiotic resistant and biofilm forming pathogens in raw meat and its environment in retail shops in Pakistan, which could play a role in the spread of antimicrobial resistance amongst food-borne bacteria.